Manfaat Blended Learing sebagai Upaya Peningkatan Efisiensi Pembelajaran dalam Manajemen Pendidikan - Anaconda Bangkara (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
Blended learning is a learning approach that combines face-to-face methods with online technology. This learning model is developing rapidly along with advances in information technology and the need for a flexible education system as part of the implementation of contemporary Educational Management. This study aims to describe the benefits of blended learning for students in improving the quality of the learning process in higher education. The method used is descriptive analysis with data collection through questionnaires and literature studies from previous studies. The results show that blended learning provides various benefits, including increasing flexibility in study time, encouraging students to be more independent, expanding access to digital learning resources, and strengthening academic interactions with both lecturers and fellow students. The analysis also found that blended learning not only adds variety to learning methods but also contributes to building 21st-century skills such as self-directed learning, digital literacy, and collaboration skills, which can be considered part of current learning innovation. These findings indicate that blended learning is a relevant and effective learning strategy to address the needs of higher education in the digital era.